Implementation of Dijkstra's Algorithm for Nearest Location Search on Fire Extinguishing Robot - Narji, Mohammad; Setiadi, Dedi (Jurnal Teknologi Informatika dan Komputer, 2025)
Today's technological knowledge has experienced a lot of progress, including in robotic technology. Of course, this field is becoming more interesting to study, seeing its increasingly widespread use in various aspects of human life that are increasingly automated. Real-life automation in machine representation is a value in itself from the implementation of a robot. Along with the development of the era, the world of information technology is currently developing very rapidly. In line with the rapid development of information technology, the need for time efficiency is a very important issue today. One of them is finding the shortest path from the original location to the destination location. In achieving optimal time efficiency, good management is needed by applying directed concepts and increasingly modern and sophisticated technology. Information media is very much needed in a computerized way to make it easier for fire extinguishing robots to find the location of fire points. The use of the Dijkstra Algorithm in the Nearest Route Search Application was chosen to be applied to the fire extinguishing robot application, to solve problems step by step in finding the nearest route. The theory used in this study uses Graph theory, Dijkstra's Algorithm. The purpose of this study is to find out how fire extinguishing robots find the shortest route and how the Dijkstra algorithm method can be used to find the location of the fire source with the shortest route.